Chickpea Genotypes Contrasting for Vigor and Canopy Conductance Also Differ in Their Dependence on Different Water Transport Pathways - Sivasakthi, Kaliamoorthy; Tharanya, Murugesan; Kholová, Jana; Wangari Muriuki, Ruth; Thirunalasundari, Thiyagarajan; Vadez, Vincent (Frontiers in Plant Science, 2017)
Lower plant transpiration rate (TR) under high vapor pressure deficit (VPD) conditions and early plant vigour are proposed as major traits influencing the rate of crop water use and possibly the fitness of chickpea lines to specific terminal drought conditions, this being the major constraint limiting chickpea productivity. The physiological mechanisms underlying difference in TR under high VPD and vigour are still unresolved, and so is the link between vigour and TR. Lower TR is hypothesized to relate to hydraulic conductance differences. Experiments were conducted in both soil (Vertisol) and hydroponic culture. The assessment of the TR response to increasing VPD showed that high vigour genotypes had TR restriction under high VPD, and this was confirmed in the early vigour parent and progeny genotype (ICC 4958 and RIL 211) having lower TR than the late vigour parent and progeny genotype (ICC 1882 and RIL 022). Inhibition of water transport pathways (apoplast and symplast (aquaporins)) in intact plants led to a lower transpiration inhibition in the early vigour / low TR genotypes than in the late vigour / high TR genotypes. De-rooted shoot treatment with an aquaporin inhibitor led to a lower transpiration inhibition in the early vigour / low TR genotypes than in the late vigour / high TR genotypes. Early vigour genotypes had lower root hydraulic conductivity than late vigour / high TR genotypes. Under inhibited conditions (apoplast, symplast), root hydraulic conductivity was reduced more in the late vigour / high TR genotypes than in the early vigour / low TR genotypes. We interpret that early vigour / low TR genotypes have a lower involvement of aquaporins in water transport pathways and may also have a smaller apoplastic pathway than high TR genotypes, which could explain the transpiration restriction under high VPD and would be helpful to conserve soil water under high evaporative demand. These findings open an opportunity for breeding to tailor genotypes with different “dosage” of these traits toward adaptation to varying drought prone environments.